2011
DOI: 10.1093/cid/ciq247
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of Hepatitis B Virus (HBV) Infection through Blood Transfusion from Blood Donors with Occult HBV Infection

Abstract: OHB donor blood infectivity was shown in our animal and human studies. However, the risk of HBV transmission in humans was low, especially from blood products obtained from donors with OHB who were anti-HBs positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 21 publications
9
80
0
1
Order By: Relevance
“…From 2010 to 2015, many blood banks began to implement NAT screening. The prevalence of HBV DNA among seronegative blood donations has been reported in other countries and several blood banks of China91011. However, to date, no study has reported on the frequency of HBV DNA positivity among seronegative blood donors throughout China.…”
mentioning
confidence: 79%
“…From 2010 to 2015, many blood banks began to implement NAT screening. The prevalence of HBV DNA among seronegative blood donations has been reported in other countries and several blood banks of China91011. However, to date, no study has reported on the frequency of HBV DNA positivity among seronegative blood donors throughout China.…”
mentioning
confidence: 79%
“…However, one in four recipients of BD1 FFP and three/six recipients of BD2 FFP were not infected, suggesting that in these OBIs with very low viral load, fluctuation of HBV DNA levels was present as described in OBI with higher viral load 7 13 16. This series of patients provided the opportunity to revise the predicted OBI infectious dose of 1049 copies (range 117–3441) or 197 IU on the basis of clinical data,9 and of 316 copies or ~60 IU when derived from a mathematical model 23…”
Section: Discussionmentioning
confidence: 99%
“…In South East Asia, where genotypes B and C are prevalent, up to 90% of the population has evidence of past exposure to HBV 5–7. The prevalence of OBI previously reported among blood donors in Asia is 1:570–1:7517 in China,4 8 1:3248 in Hong Kong,9 1:894–1:1029 in Taiwan7 10 and 1:3832 in Thailand 11…”
Section: Introductionmentioning
confidence: 94%